What Personalized Medicine Humans Need and Way to It ——also on the Practical Significance and Scientific Limitations of Precision Medicine - Yuan B (Dove Medical Press, 2022)
Bing Yuan HK Modern Chinese Medicine R&D Center, Kowloon, Hong KongCorrespondence: Bing Yuan, HK Modern Chinese Medicine R&D Center, Room 2, 7/F Kiu Kin Mansion, 566-568 Nathan Road, Kowloon, Hong Kong, Email greenisland@vip.163.comAbstract: The rise of precision medicine has opened up a broad space for the development of modern medicine and has also given practical significance to the concept of personalised medicine. Precision medicine is establishing a personalized disease classification system that differs from the traditional system. However, the research progress of precision medicine in recent years is far from satisfactory: There are few disease types that can be attributed to the abnormality of a single target; the effects of current'precision' medications are not ideal, and various side effects remain unavoidable. The methodology of precision medicine is still reductionist, and it would not solve the integration problem of clinical treatment but rather would increase the difficulty of integration. Therefore, the precision medicine approach is not a feasible way to build a personalised medicine system. Based on the analysis and demonstration of the scientific limitations of precision medicine and the consistency of traditional Chinese medicine (TCM) and complexity science methods, this paper draws on the concepts and methods of cybernetics and complexity science, and proposes a fresh set of ideas and methods for the development of personalised medicine. The conclusion is as follows: Along the path of precision medicine, ideal personalised medicine cannot be achieved; what people ultimately need is personalised medicine that can achieve holistic integration. On the basis of TCM with the characteristics of holistic integration and personalisation, and according to scientific norms and the principle of evidence, building a theoretical model and state description system grounded in empirical evidence is the best way to establish a personalised medicine system.Keywords: personalised medicine, precision medicine, disease classification, state medicine, holistic medicine